FAKTOR YANG MEMPENGARUHI KEPADATANLALATDIBAGIAN INSTALASI GIZI RSUD WALUYO JATI KRAKSAANKABUPATENPROBOLINGGO TAHUN 2014 - Aditya Bagus Candra Trisna; Sukiran Al Jauhari; Suparlan . (Poltekkes Kemenkes Surabaya, 2015)
Nutrition division of the Rumah Sakit Umum Daerah Waluyo Jati at Kraksaan is a quantity food procurementand processing. During the procurement and processingof food there is a risk of disease transmission. It canoccur when food and food materials are purchased, storage of processed food, or when food are served inunsanitary state. In terms of siting, the nutrition division is located very close to solid waste holding center,medical waste incineration site and also close to the morgue. Flies found in any room in the nutrition divisionare capable of transmitting diseases. The purpose of this study was to determine the factors that determinethe density of flies in the Nutrition division of the RumahSakit Umum Daerah Waluyo Jati at Kraksaan.This is a non-experimental research and data are analyzed in the study using descriptive procedures Thismethod is normally used to solve or answer problems faced in-the present situation. This study was aimed toidentify the factors that influence fly population in the Nutrition Division of the Rumah Sakit Umum DaerahWaluyo Jati Kraksaan.Resultsof the measurement on the density of flies at the Nutrition Division of the RSUDWaluyo Jati measuredby fly grills are as follow: Fly density was highest at washing room, food processing room, and the receptionof raw materials. Type of food preffered by flies were various types of vegetables, meat, and food scrappingsretrieved from patients. Type of waste preferred by flies is wet garbage. The average temperature was 26°Cat the time of the study, while the average humidity is 73%.In order to control flies at the Nutrition Division, it was suggested to the hospital for immediate repair ofhigyene and sanitation facilities at the Nutrition Division by installing fly traps, such as light tra-psor fly traps,practicing clean and healthy behavior by all employess, move or rearrange room assignment, considering thatthe Nutrition division was too close to solid waste temporary holding site, incinerator, and morgue.